CHILDREN'S CHARACTER EDUCATION AMONG FISHERMEN'S FAMILIES IN JATIREJO VILLAGE, LEKOK DISTRICT, PASURUAN REGENCY - Yuniar Mujiwati (Jurnal Scientia, 2022)
This research aim to implement character education for the children of fishermen in Lekok Pasuruan, and describe the character of educational factors for the children of fishermen in Lekok Pasuruan. This research use a qualitative with the field research type. Sources of data in this research using primary and secondary data sources. Data collection techniques in this research using; interview method, observation method, and documentation method. While the data analysis technique use descriptive qualitative data analysis. The result of the research is an educational strategy which given by the fishing community to children, through habituation and example in everyday family life, such as religion, independence, and responsibility. This including the environmental factor in character education of fishermen's children, the factor of habituation, example and awareness. The instinct factors that occur in the family environment are very good, because from generations they set a good example for each of their children. The habit factor of fishermen's children looking at the usual family environment with family kindnesses.